PEMBERIAN SANKSI DANA ZAKAT KEPADA BENDAHARA PEMERINTAH DI PAGALARAM - Fitria Kusumawardhani (Faculty of Law - Tarumanagara University, 2019)
This study aims to find out and analyze the granting of alms charity funds to the Government Treasurer in Pagalaram City for the implementation of zakat funds carried out by the Government Treasurer.The research method used is normative law, namely the legal systematics that identifies the basic meaning in law. analyzed using statistics or mathematics or the like, but describe descriptively from the data obtained and also the method of inductive thinking is the conclusion that a statement or dalili that is special becomes a general statement or case, the data source uses secondary data namely Primary Legal Material namely, Secondary Legal Material Research and tertiary Legal Material.The purpose of this writing is to find out and identify and understand about the granting of zakat alms (BAZ) sanctions to government treasurers in Pagalaram city. Approach to Law Number 20 of 2011 concerning the Eradication of Corruption Crimes and also a theoretical approach to zakat and the Regulation of the Financial and Development Supervisory Agency.The results of this study indicate that the embezzlement of funds carried out by the Government Treasurer on zakat funds is in the place of the Zakat Agency (BAZ) which should be used for people who need financial assistance, there can be empowered for something useful for the community to can be said to be less capable in income / income distributed by the Amil Zakat Agency (BAZ).